2013
DOI: 10.1039/c3nr01119d
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of plasmonic and magnetic properties in Au89Fe11 nanoalloys

Abstract: We describe an environmentally friendly, top-down approach to the synthesis of Au 89 Fe 11 nanoparticles (NPs). The plasmonic response of the gold moiety and the magnetism of the iron moiety coexist in the Au 89 Fe 11 nanoalloy with strong modification compared to single element NPs, revealing a non-linear surface plasmon resonance dependence on the iron fraction and a transition from paramagnetic to a spin-glass state at low temperature. These nanoalloys are accessible to conjugation with thiolated molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(166 citation statements)
references
References 85 publications
10
156
0
Order By: Relevance
“…[97] In the same catalysis, Yang et al compared as eries of Ni and Pt based alloy NPs and showed that most of the alloys demonstrated higher catalytic performance than either pure Pt or Ni metals. [99,100] An additional advantage in the alloy NP system is that alloying using cheaper transition metals largelyr educes the use of expensive noble ones, such as Pt,l eadingt oamoree conomicm aterial. For instance, AuFe alloys with appropriate elemental ratio combine the unique features of both the SPR of Au NPs and magnetic property of Fe, which have demonstrateds ignificant application potential in both catalysis and magneto-opticalr esponses.…”
Section: Alloy Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…[97] In the same catalysis, Yang et al compared as eries of Ni and Pt based alloy NPs and showed that most of the alloys demonstrated higher catalytic performance than either pure Pt or Ni metals. [99,100] An additional advantage in the alloy NP system is that alloying using cheaper transition metals largelyr educes the use of expensive noble ones, such as Pt,l eadingt oamoree conomicm aterial. For instance, AuFe alloys with appropriate elemental ratio combine the unique features of both the SPR of Au NPs and magnetic property of Fe, which have demonstrateds ignificant application potential in both catalysis and magneto-opticalr esponses.…”
Section: Alloy Npsmentioning
confidence: 99%
“…[78,93,94,[100][101][102][103][104][105][106] Because Ag and Au possess very similarl attice constants, these two elements are highly miscible over the entire composition range. [78,93,94,[100][101][102][103][104][105][106] Because Ag and Au possess very similarl attice constants, these two elements are highly miscible over the entire composition range.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the first ''cocktail recipe'', dual functions can easily be obtained by either synthesis of alloy nanoparticles or by doping oxide nanoparticles. When alloy nanoparticles are used as the target material, it is possible to combine the plasmonic properties of Ag or Au with the magnetic properties of Fe [58,62,78]. This coexistence of properties can be used for imaging techniques such as multimodal SERS-MRI-CT [62].…”
Section: Dual Functionsmentioning
confidence: 99%
“…To this aim, the exploitation of iron-doped silver nanoparticles (NPs) synthesized by laser ablation of abulk bimetallic iron-silver target immersedi ne thanol is described. [52] Nanostructures with magnetic andp lasmonic responses obtained so far by this method include gold-iron [14,18,53,54] and silver-iron nanoalloys, [25] nanocrescents, [54] andc ore-shell structures with either ap lasmonic core and magnetic oxide shell [54] or am agnetic iron core and plasmonic shell. These iron-silver NPs show SERS performances, ar eady responset oe xternalm agnetic fields and complete flexibility in surface coating.…”
Section: Introductionmentioning
confidence: 99%